Discursive Experiment as a Method of Onym Discourse Actualization - Elena Pozdnyakova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2022)
The article presents the description of the methodology of carrying out a discursive experiment as a consecutive study necessary for the expanding of a proper name discourse. Proceeding from the assumption that the proper name actualizes the onym discourse, the author put forward the following model of a discursive experiment: stage 1 – an associative experiment; stage 2 – dialogical text modelling; stage 3 – monological text modelling. The names of urban commercial objects (ergonyms) were selected as the material for the study. This group of onyms was chosen as one of the most frequently used in urban spatial discourse and functioning both in everyday and in institutional discourse. The associative experiment resulted in receiving the reactions, which represent the initial stage of onym discourse expanding. The derivational, paradigmatic and syntagmatic mechanisms were used at this stage. At the second stage, dialogical reactions were received. The communicative models of dialogue composition were conditionally divided into the models of opposition, comparison and dissemination. As a result of the third stage of the experiment, texts were received, mainly of a fantasy nature. The experiment proved that the proper name is not only an abridged text, but a compression of a variety of texts, which has the potential of unfolding in dynamics and creates a kind of discursive field of the onym.